Effects of Pilates Reformer Core and Mat Core Exercises on Standing Posture Alignment - Gyeongseop Sim; Donghoon Kim; Hyeseon Jeon (Korean Research Society of Physical Therapy, 2022)
Background: Pilates exercises are used for body shape correction because they can achieve correct posture alignment through spinal stabilization.Objects: This study aimed to determine whether the use of reformers increases the effective-ness of Pilates core exercises on body alignment in standing.Methods: The study included 30 women without known diagnoses of musculoskeletal and neurological disorders or cancer. Those who had taken more than 10 Pilates lessons were ex-cluded. The participants were randomly assigned to either the reformer exercise group or the mat exercise group, and interventional Pilates exercises were performed for 60 minutes a day, three times a week, for a total of 8 weeks. Ten movements of the reformer and mat Pilates core exercise programs were included. Exbody® 9100 MOMI musculoskeletal analysis equipment (Exbody Inc.) was used to assess the alignment of the standing posture in the frontal plane.Results: As a result of comparing the differences within and between the groups before and after the intervention using the two-way mixed analysis of variance test, height differences in the head, pelvis, left and right, shoulders, scapulas, knees, and ankles in the frontal plane after the intervention were found in both groups. For example, the left-right symmetry of the body alignment in the standing posture was significantly improved within each group (p < 0.05). However, no significant difference was found between the groups (p > 0.05).Conclusion: Both the reformer and mat Pilates core exercises were effective for standing posture alignment, which has clinical significance. If an exercise program is developed based on the analysis of movements necessary for posture improvement and the target muscles to be strengthened, the same effect can be achieved only with mat exercise without using the reformer equipment at the beginner stage.